2009
DOI: 10.1021/jp811020s
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Reduced Ultrathin TiOx Polar Films on Pt(111)

Abstract: The structure of well-ordered reduced TiOx nanolayers (NLs) on Pt(111), prepared by reactive evaporation of Ti in an oxygen background and postannealed in different conditions, is discussed on the basis of experimental and theoretical data. All of the observed NLs are formed by a wetting 2D Ti−O bilayer where the Ti atoms are at the interface and the O atoms form the topmost layer. Different structures and stoichiometries depend on the actual Ti coverage and on the conditions of the postannealing. They represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
92
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 35 publications
10
92
0
Order By: Relevance
“…The BE parameter allows a straightforward classification of the TiO x structures into reduced and oxidised, respectively. Density functional (DF) calculations, that provided an accurate estimate of the TiO x stoichiometry, confirm the XPS results [13][14][15][16]. Recently we also investigated the structure of the occupied electronic levels of the TiO x ultrathin films by means of valence band (VB) photoemission spectroscopy (VB-PES) [11].…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…The BE parameter allows a straightforward classification of the TiO x structures into reduced and oxidised, respectively. Density functional (DF) calculations, that provided an accurate estimate of the TiO x stoichiometry, confirm the XPS results [13][14][15][16]. Recently we also investigated the structure of the occupied electronic levels of the TiO x ultrathin films by means of valence band (VB) photoemission spectroscopy (VB-PES) [11].…”
Section: Introductionsupporting
confidence: 61%
“…The notation used to label the phases is determined by to the shape of the surface unit cell or to their appearance in STM. This notation is consistent with the one used in previous experimental and theoretical studies [10][11][12][13][14][15][16]20]. The Ti coverage is gauged from Ti 2p XPS intensity (peak area) normalised to the average XPS intensity of the wagon-wheel w structure, which serves as a reference (see Fig.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…[9,10] On the other hand, when a higher oxygen background is used, fully stoichiometric NSs of different thickness can be prepared, where oxygen atoms are located at the interface with the Pt substrate. [11][12][13] In particular, we have already shown that a lepidocrocitelike [14] fully stoichiometric NS (named rect-TiO 2 according to the previously reported nomenclature) can be formed under strongly oxidative conditions (P O2 = 1 10 À4 Pa) on both Pt (111) and (1 2)-Pt(110) surfaces: [11][12][13] On the former it has been found that the NS is characterized by a rectangular unit cell and that the film is incommensurate with respect to the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…These have been extensively studied by the authors and reviewed previously [11,12,15,55,134], so that we do not repeat their discussion here and we refer the reader to these previous reviews.…”
Section: Electronic Ground State (Occupied Orbitals)mentioning
confidence: 99%